Genealogi Wabah dalam Cerita-cerita Dewi Sekardadu: Kajian Sastra Pandemik - Mashuri Mashuri; Jauharoti Alfin (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2021)
This research traces the genealogy of the wabah (pandemic) in Dewi Sekardadu's stories. Dewi Sekardadu’s story in this study is taken from the Javanese writing tradition. This paper aim to describe the origin of the wabah in the story (Dewi Sekardadu) and the power relations of knowledge in Java from the point of view of origin and meaning. The theory used is triangulation folklore theory, comparative literature and archo-genealogy of knowledge. The results were (1) almost all Javanese chronicles or chronicles always included Dewi Sekardadu's story because it was always mentioned in the stories of Maulana Ishak or Seh Wali Lanang and Sunan Giri; (2) the position and causes of the wabah in Dewi Sekardadu's storyline in the old writing tradition varied depending on the writing period; and (3) the genealogy of the wabah in Dewi Sekardadu's stories can be traced to several previous Javanese sources or literature, namely the stories of prophets, guardians, and pre-Islamic treasures in Java.